2016
DOI: 10.1093/qjmed/hcw169
|View full text |Cite
|
Sign up to set email alerts
|

Miliarial gout: a rare presentation of extensive cutaneous tophi

Abstract: Gout is a systemic disorder characterized by hyperuricemia and recurrent arthritis, most involvement of ankles, midfoot joint and first metatarsophalangeal joint, with monosodium urate crystals deposition in synovial fluid and other tissues. We present a case of 53-year-old male, who had several nontender, white-yellow papules and plaques over his elbows, knees and arms with chalk-like substances and crust on inflammatory base wax and wane in the past 2 years. Upon histopathology examination of the skin lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…6 Regarding miliary gout, unusual locations of tophi (eg, chest, abdomen, back, arms, forearms, thighs) should draw attention to this entity because they have been associated with it. 8,10,12 Thus, in contrast to the peripheral sites, low distal temperature does not appear to play a major role in the pathophysiology of such cutaneous lesions. Hypotheses regarding the clearance ability of MSU by tissue macrophages have been put forward, but the pathogenesis of this clinical expression remains unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 Regarding miliary gout, unusual locations of tophi (eg, chest, abdomen, back, arms, forearms, thighs) should draw attention to this entity because they have been associated with it. 8,10,12 Thus, in contrast to the peripheral sites, low distal temperature does not appear to play a major role in the pathophysiology of such cutaneous lesions. Hypotheses regarding the clearance ability of MSU by tissue macrophages have been put forward, but the pathogenesis of this clinical expression remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…It is a rare cutaneous manifestation of tophaceous gout since only a few cases have been reported. [7][8][9][10][11][12][13][14] To our knowledge, Shukla et al 7 documented the first case in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed 11 cases of miliarial gout reported in the literature (including the current case), 2–11 with a mean age of 50 (SD = 15) years old, and male preponderance (82%) (Table 1). Of note, 64% of reported cases had no known history of gout, and miliarial gout could be the first manifestation of tophaceous gout.…”
Section: Discussionmentioning
confidence: 99%
“…Miliarial gout is a rare variant of the cutaneous form of gout consisting of milialike papules, first described by Shukla et al in 2007. 2 We reviewed 11 cases of miliarial gout reported in the literature (including the current case), [2][3][4][5][6][7][8][9][10][11] with a mean age of 50 (SD = 15) years old, and male preponderance (82%) (Table 1). Of note, 64% of reported cases had no known history of gout, and miliarial gout could be the first manifestation of tophaceous gout.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis is poorly understood. In our review of 23 reported cases of extensive extra-articular dermal/subcutaneous tophi (including the present case), [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], the majority of patients were male (87%) and Asian (57%), (Table 1). There was fairly equal representation from Asian countries with high gout prevalence (Taiwan) as well as those with low prevalence (China, South Korea, Philippines, Vietnam), [19].…”
Section: Case Discussionmentioning
confidence: 99%